The coronavirus conundrum – Consequences of the SARS-CoV-2 infection in humans – The brain – Pregnant women and newborns - Romero, José Pacheco (2023)
The SARS-CoV-2 virus continues to replicate. Its new variants would not be causingthe deaths and serious hospitalizations of the years 2020-2022, so the World HealthOrganization (WHO) has declared the end of the state of health emergency. Until May24, 2023, the WHO coronavirus dashboard shows more than 766 million confirmedcases, and about 7 million deaths in the world, with greater concentration in Europe,Western Pacific, and America (especially the U.S.A. and Brazil). Europe and Chinaprepare for new virus breakthroughs. Therefore, health precaution is recommended,as well as compliance with vaccination and boosters, and the development of newvaccines. We comment on the fragility of randomized trials published in the first twoyears of the pandemic, as well as recent findings of which patients with COVID coulddevelop long COVID. It is important to know the new scopes on the affectation ofthe coronavirus on the pregnant woman, the fetus and the neonate and the initialfollow-up of the latter.